Investigation of Online Peer to Peer lending as a means to facilitate entrepreneurial finance in South Africa - Pholo, Makgowe Adam (My University, 2021)
With technological advancement in the financial sector over the last few years, there now exists digital business loan providers for both SMMEs and retail borrowers. These digital loans have expanded the scope of alternative sources of borrowing and funding alike. The adoption of these fintech funding models has been somewhat slow in South Africa, but if the success of other countries' adoption of these models, particularly peer to peer lending, is anything to go by, this fintech funding model could fill the gap that currently exists in SMME funding. Data is gathered from SMMEs as well as potential investors on the usage of Online Peer to Peer lending as both a funding mechanism as well as an investment proposition. The purpose of this data gathering -- via a survey --was to obtain Online Peer to Peer participants' views and/or perceptions about the effectiveness of online peer to peer lending, awareness of alternative (particularly fintech) funding models as well as their receptiveness to conducting financial transactions online. The survey found that the majority of entrepreneurs and investors believe that online peer to peer lending can bridge the financing gap left by traditional financing institutions in South Africa. Awareness of available fintech financing methods in South Africa is very low amongst both entrepreneurs and retails investors according to the research results in this paper. This suggests more could be done around socializing this form of financing to the general populace. The findings of the research also suggested overall that there is a viable business case for alternative financing for SMMEs in South Africa. In addition, the results of the survey indicated that the slow adoption of this fintech financing models in South Africa creates an opportunity for new fintech start-ups to participate in this market due to the low barrier to entry
A dissertation submitted to the Wits Business School, Faculty of Commerce, Law and Management, University of the Witwatersrand in partial fulfilment of the requirements for the degree of Master of Management (in Finance and Investments), 2021
Keywords: Online Peer to peer lending; P2P lending; Rowdfunding; Fintech; Investor; Lender; SDG-8: Decent work and economic growth